Reality shock and its associated factors among newly graduated nurses in China: A cross-sectional study - Liping Li; Zhangyi Wang; Xiaochun Tang; Jun Qu; Huifang Zhou; Lamei Chen; Hongxia Wu; Shuguang Tan; Mengsu Liu (PLoS ONE, 2026)
Background Newly graduated nurses often experience a transition period marked by reality shock, which can adversely affect their professional retention and career development. However, the associated factors remain incompletely understood, and there is a notable gap in evidence regarding the role of the impostor phenomenon in this context. Objectives To investigate the reality shock among newly graduated nurses and identify its associated factors, with a specific focus on the impostor phenomenon. Methods A cross-sectional design was implemented, and the high-quality reporting of the study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement. From July 2024 to January 2025, a total of 381 newly graduated nurses were recruited from 3 tertiary grade-A hospitals in China by convenience sampling. The inclusion criteria required nurses to hold a valid nurse qualification certificate, be registered at the hospital, have a clinical working time of ＜ 1 year, and provide informed consent while cooperating with investigators. Exclusion criteria applied to hospital trainees, standardized training personnel, and personnel not on duty for various reasons. The Demographic Characteristics Questionnaire, Reality Shock Scale for Newly Graduated Nurses, and Clance Impostor Phenomenon Scale were used. The data was analyzed using descriptive statistics, univariate analyses, correlation, and multiple linear regression analysis. Results The total scores for reality shock and impostor phenomenon were 93.66 ± 38.94 and 44.19 ± 16.94, respectively. Reality shock was positively correlated with the impostor phenomenon ( r = 0.635, p < 0.01). Multiple linear regression analysis showed that educational level, monthly income, number of night shifts per month, and impostor phenomenon were the main factors affecting the reality shock among newly graduated nurses (all p < 0.01), accounting for 51.80% of the total variance. Conclusion This study identified a moderately high level of reality shock among newly graduated nurses. Key determinants associated with this shock included educational level, monthly income, number of night shifts per month, and impostor phenomenon. Nursing management should develop targeted interventions addressing these modifiable factors, particularly impostor phenomenon, which may help mitigate reality shock and facilitate successful career adaptation among newly graduated nurses.